Advanced Human Capital Structure, Industrial Intelligence and Service Industry Structure Upgrade ——Experience from China's Developments. Issue 5 (9th April 2023) - Ma, Hongmei; Sun, Yiwen; Yang, Lingxiao; Li, Xiuzhen; Zhang, Yun; Zhang, Fang
ABSTRACT: This study investigates the relationship between advanced human capital structure, industrial intelligence, and service industry structure based on China's development from provincial data from 2008 to 2019. It finds that the advanced human capital structure can significantly promote the structural development of the service industry. Meanwhile, there is some heterogeneity in the impact of advanced human capital structure on the service industry. In the eastern region and high level of elemental market development in China, advanced human capital structure has a more significant contribution to the service industry structure upgrade. More importantly, industrial intelligence will play a positive moderating effect on the process of upgrading the human capital structure to the service sector structure. Further, the effect of advanced human capital structure on the service industry's development depends on the threshold of industrial intelligence. When industrial intelligence exceeds the threshold, it can strengthen the "promotion effect" of advanced human capital structure.